2019
DOI: 10.3390/ijerph16173215
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Pilgrims Regarding Heat-Related Illnesses during the 2017 Hajj Mass Gathering

Abstract: The Hajj mass gathering attended by over two million Muslim pilgrims from around the world is a risk for heat-related illnesses (HRIs). We investigated the knowledge, attitude and practice (KAP) of pilgrims attending the 2017 Hajj regarding HRIs and their prevention. Adult pilgrims (1801) from six countries in Africa, Asia and the Middle East were interviewed using a structured questionnaire. Pilgrims had a mean age of 47.2 years (SD = 12.6) and a male:female ratio of 2.2:1. Over 83% declared having at least a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 27 publications
2
17
1
1
Order By: Relevance
“…Reported levels of education among pilgrims varied depending on the studied populations. One study among pilgrims from South Africa, Nigeria, Pakistan, Egypt, Iraq, and Indonesia in 2017 found that 83.7% had secondary or higher education [ 26 ]. A similarly high proportion was reported among Indonesian and Australian pilgrims [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reported levels of education among pilgrims varied depending on the studied populations. One study among pilgrims from South Africa, Nigeria, Pakistan, Egypt, Iraq, and Indonesia in 2017 found that 83.7% had secondary or higher education [ 26 ]. A similarly high proportion was reported among Indonesian and Australian pilgrims [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A scoring system was developed to score the knowledge and attitude of study participants, as described previously. 36 , 37 Briefly, incorrect/inappropriate were given a 0 score, while one point was given for choosing the correct/appropriate answer; a correct/appropriate response was based on current literature and the good attitude. For multiple-choice questions with more than one correct answer, one score was given for the correct/appropriate response and for not choosing the incorrect/inappropriate responses.…”
Section: Methodsmentioning
confidence: 99%
“…Risk of heatrelated illness is exacerbated by age, comorbidities such as diabetes, 95 and reluctance among some people to adopt hydration and other preventative practices (eg, umbrellas) due to misconceptions about compatibility with Hajj rituals. 96…”
Section: Mass Gatheringsmentioning
confidence: 99%